Determination of Brand Trust by Social Media Advertising and Electronic Word of Mouth - Yuliana, Lingga; Trigani, Ida; Larasati, Nike; Nurjanah, Siti (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2025)
The purpose of this study was to partially ascertain how social media advertising and electronic word-of-mouth factors affected brand trust.  However, there hasn't been much research done on how social media advertising affects brand trust.  Customers consider trust before making a purchase, so this gap needs to be investigated.  The author has opted for quantitative research as the research methodology.  Purposive sampling is used in the sampling procedure. In all, 343 individuals ages 18 to 40 who lived in Jabodetabek participated in this survey.  The research was carried out in March 2025.  Men and women who wore sneakers from the labels Aerostreet and made up the respondents. The data source distributes questionnaires via Google Form in order to obtain primary data.  Using the SmartPLS data processing tool version 4.1.0.0, the data analysis method employs Partial Least Square.  The study's findings demonstrate that social media advertising significantly and favorably affects brand trust.  However, brand trust is significantly and favorably impacted by electronic word-of-mouth.  This research offers managerial understanding of corporate operations.  The findings of this study can be used by local brand marketers to leverage the potential of electronic word-of-mouth and social media advertising in an attempt to build brand trust, which will improve company. Online advertising can help build trust, which is always essential for business success. Marketers use advertising to get their messages out there.  Additionally, customers decide how to examine information in social network suggestions and communications.